Editorial: autoimmune diseases in microscopic colitis—how does this information help clinicians?. Issue 10 (26th October 2021) - Pardi, Darrell
LINKED CONTENT: This article is linked to Wildt et al paper. To view this article, visit https://doi.org/10.1111/apt.16614